Frequency and Genotyping of High Risk Human Papilloma Virus Among VIA Positive Women Attending At Colposcopy Clinic, Chittagong Medical College Hospital - Sharmin, Dina; Chowdhury, Fahmida Islam; Meher, Subrina; Akter, Farzana; Tabassum, Tamanna; Chowdhury, Shahanara; Akter, Shahena (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Worldwide, cervical cancer is one of the most important cancers in women, being responsible for 569,847 new cases and 311,365 related deaths in 2018, according to GLOBOCAN. There are several methods to recognize HPV. Among them, PCR has been widely used to detect HPV DNA. Purpose of this study was to determine the frequency and genotyping of the high risk Human Papilloma Virus (16, 18) among VIA positive women attending colposcopy clinic. Materials and methods: This was a cross sectional study and was conducted in the Colposcopy Clinic, Department of Obstetrics and Gynecology of Chittagong Medical College Hospital from January 2021 to June 2021. During the study period 50 VIA positive women attending colposcopy clinic were taken as study subjects. Data were collected by a predesigned case record form. Analysis was done using computer software SPSS version 25. Results: Out of 50 VIA positive women, the mean age was 37.14 ± 4.5 years. Colposcopy report of VIA positive patients shows that 41 (82%) had normal, 8 (16%) CIN I and 1 (2%) CIN III. PCR analysis shows that 8 (16%) positive. Molecular genotyping of PCR positive patients shows that 5 (62.5%) were infected by HPV 16 and 3 (37.5%) were infected by HPV 18. There was no significant difference between colposcopy findings and PCR findings. Age at marriage, age at full term pregnancy, H/O husband living abroad and husband having promiscuous relationship showed significantly greater chance of having positive result by PCR analysis. Conclusion: Age at marriage, age at first pregnancy, H/O husband living abroad and husband having promiscuous relationship showed greater chance of having HPV infection. Early detection of HPV and early diagnosis of precancerous lesions can lower the chance of cervical cancer. JCMCTA 2023 ; 34 (1) : 85-89